Quality of life among thalassaemia children, adolescent and their caregivers - Munirah Ismail; Choong, Yin Chun; Noor Aini Mohd Yusoff; Suzana Shahar; Zahara Abdul Manaf; Roslee Rajikan; Zarina Abdul Latiff; Hishamshah Mohd Ibrahim; A. Rahman A. Jamal (Universiti Kebangsaan Malaysia, 2013)
In thalassaemic patients, the impact of the disease especially on quality of life (QOL) of the caregivers in Malaysia has not been established. This study was conducted to assess the health-related quality of life (HRQOL) of thalassaemia patients and their caregivers in order to explore factors affecting their QOL. A cross-sectional study was conducted on 75 thalassaemic children and adolescents aged between 7 and 18 years old and their caregivers. The PedsQLTM 4.0 generic core scales questionnaire was administered to both thalassaemic children and their caregivers while the health questionnaire EQ 5D was given to caregivers only. The subjects were recruited from Hospital Kuala Lumpur (HKL) and Universiti Kebangsaan Malaysia Medical Centre (UKMMC). The results revealed that the mean of psychosocial HRQOL score in patients (63.91±14.65) was significantly lower than parent proxy reports (67.14±10.48) (p=0.008). The school functioning score (50.59±15.31) was the lowest of the psychosocial measure, followed by emotional functioning (59.92±16.83) and social functioning (78.01±13.92) score. The patients’ pre-transfusion haemoglobin concentration was significantly associated with their QOL (p=0.02). Having more children, higher numbers of thalassaemic children and lower educational level of caregivers were associated with poorer QOL. In conclusion, caregivers underestimated the QOL of their thalassaemic children. The school functioning was affected the most domain. There is a need to improve the QOL of thalassaemic children and their caregivers.